2018
DOI: 10.6004/jnccn.2017.7046
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Risk Factors for Adverse Metabolic Outcomes in North American Testicular Cancer Survivors

Abstract: Testicular cancer survivors (TCS) are at significantly increased risk for cardiovascular disease (CVD), with metabolic syndrome (MetS) an established risk factor. No study has addressed clinical and genetic MetS risk factors in North American TCS. TCS were aged<55 years at diagnosis and received first-line chemotherapy. Patients underwent physical examination, and had lipid panels, testosterone, and soluble cell adhesion molecule-1 (sICAM-1) evaluated. A single nucleotide polymorphism in rs523349 (5-α-reductas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 75 publications
0
21
1
4
Order By: Relevance
“…7 The prevalence of metabolic syndrome in TCS and its risk factors have been reviewed in detail elsewhere. 17 In our investigation, the cumulative dose of cisplatin did not correlate with the prevalence of hypogonadism. Other studies 41,42 have reported a higher prevalence of hypogonadism in TCS who received higher doses of cisplatin.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…7 The prevalence of metabolic syndrome in TCS and its risk factors have been reviewed in detail elsewhere. 17 In our investigation, the cumulative dose of cisplatin did not correlate with the prevalence of hypogonadism. Other studies 41,42 have reported a higher prevalence of hypogonadism in TCS who received higher doses of cisplatin.…”
Section: Discussioncontrasting
confidence: 54%
“…Data on the prevalence of metabolic syndrome and its risk factors in this cohort have been previously described. 17…”
Section: Participantsmentioning
confidence: 99%
“…Our study thus addresses an important gap by identifying, specifically, cisplatin-related AHOs associated with SRH among a relatively young group of cancer survivors. Other AHOs not included in our CBM Pt score such as cardiovascular disease ( 52 , 53 ) and those related to metabolic syndromes ( 54 ) may also relate in part to cisplatin exposure; however, it is difficult to isolate cisplatin’s contribution from genetic and lifestyle factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hypogonadism was defined as testosterone levels 3 ng/mL based on crude measurement or whether the patient was on testosterone therapy. All patients who had testosterone levels > 3 ng/mL and were not on testosterone therapy were labeled as normal or high, and were grouped together as controls for the linear regression analysis, as described previously (30).…”
Section: Patient-reported Outcomes and Medical Records Data Abstractionmentioning
confidence: 99%